2014
DOI: 10.1159/000363189
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Postoperative Complications, Prolonged Length of Hospital Stay, and Short-Term Mortality in Elderly Patients with Malignant Head and Neck Neoplasm

Abstract: Purpose: To identify and assess predictors of short-term outcomes and a prolonged length of hospital stay after head and neck cancer surgery in older-old and oldest-old patients. Procedures: Patients aged ≥75 years with head and neck cancer undergoing surgery at the Brazilian National Cancer Institute from January to December 2011 were assessed regarding postoperative complications, mortality, and length of hospital stay. Results: Over the study period, 67 patients with head and neck cancer underwent surgery, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 24 publications
2
26
1
4
Order By: Relevance
“…Sun et al [13] reported similar findings, reporting that SNMMM patients aged 55 years and over had a worse prognosis. In addition, parallel results occurred in another study on malignant head and neck neoplasms [15]. As to the location of the primary tumor, in the present study, the nasal cavity was the most common site, and the nasal septum and turbinates were the most common subsites, reaffirming the findings of previous studies [16,17,18].…”
Section: Discussionsupporting
confidence: 91%
“…Sun et al [13] reported similar findings, reporting that SNMMM patients aged 55 years and over had a worse prognosis. In addition, parallel results occurred in another study on malignant head and neck neoplasms [15]. As to the location of the primary tumor, in the present study, the nasal cavity was the most common site, and the nasal septum and turbinates were the most common subsites, reaffirming the findings of previous studies [16,17,18].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, measures of ADL were not as useful at predicting complications as the frailty assessment. In contrast, Gerude et al in a study of 67 patients aged ≥75 years undergoing surgical treatment for HNC found that the increased dependence in IADLs, as measured by the Lawton Brody Scale, was significantly associated with postoperative complications (RR = 2.19, P = .005) . Our results may differ based on selection bias as patients in our practice with a significantly reduced ability to perform IADLs may not have been offered surgery.…”
Section: Discussioncontrasting
confidence: 72%
“…In terms of functional measures, the Lawton‐Brody (IADLs) and Barthel score (ADLs) were independent predictors of LOS. Similarly, Gerude et al found that the increased dependence in IADLs, was significantly associated prolonged LOS (RR = 1.9; 95% CI, 1.07–3.61, P = .02) . While the VES may be a useful tool for screening for vulnerability in older patients in a nonsurgical population in our study it was neither predictive of increased complications or LOS.…”
Section: Discussionsupporting
confidence: 38%
“…Smoking has also been shown to be a predictor of prolonged LOS after lobectomy for lung cancer in roughly 5,000 subjects [28]. Although not as robust in regards to sample size (67 patients), Gerude et al [29] demonstrated smoking to be an independent predictor of LOS after head and neck cancer surgery. A potential reason for lack of an association between smoking and LOS in our study was the overall small number/percentage of subjects who were active smokers (22/252, 8.7%).…”
Section: Discussionmentioning
confidence: 99%